2014
DOI: 10.1159/000365011
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Outcome of Patients with Lymph Node-Positive Prostate Cancer following Radical Prostatectomy and Extended Sentinel Lymph Node Dissection

Abstract: Objective: This study sought to evaluate the clinical outcome after extended sentinel lymph node dissection (eSLND) and radical retropubic prostatectomy (RRP) in patients with clinically localized prostate cancer (PCa). Subjects and Methods: From August 2002 until February 2011, a total of 819 patients with clinically localized PCa, confirmed by biopsy, were treated with RRP plus eSLND. Biochemical recurrence-free survival (RFS), cancer-specific survival (CSS), and overall survival (OS) were assessed with Kapl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 29 publications
0
9
0
1
Order By: Relevance
“…The median age was 65 with median PSA levels of 8.4 ng/mL. The median LN(n) was 25 (range [18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33]. Clinical staging assessed the tumor as extracapsular in 12 cases (11.8%) and loco-regional lymph nodes as invaded in 16 patients (15.7%).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The median age was 65 with median PSA levels of 8.4 ng/mL. The median LN(n) was 25 (range [18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33]. Clinical staging assessed the tumor as extracapsular in 12 cases (11.8%) and loco-regional lymph nodes as invaded in 16 patients (15.7%).…”
Section: Resultsmentioning
confidence: 99%
“…However, there is increasing evidence that the number of metastatic nodes can stratify subpopulations with different prognosis. In high-risk PCA, it has been shown that the lymph node burden is an independent prognostic factor associated with both cancer-specific and overall survival [10,20]. So far, clinical factors predicting the loads of LNI are important for stratifying the high-risk PCA population who is subject to multimodality treatments.…”
Section: Discussionmentioning
confidence: 99%
“…10 Muck et al showed improved survival outcomes in a large series of patients treated with RP and radioactive-guided ePLND when they had a low nodal burden. 24 Grivas et al showed that the integration of ePLND with a ICG-99m Tc-nanocolloid SN biopsy improved BCR-free rates within a median follow-up period of 28 months. 25 As this topic is controversial, several studies pointed out an oncological benefit after a more extensive LND.…”
Section: Discussionmentioning
confidence: 99%
“…In high-risk PCA, it has been shown that the lymph node burden is an independent prognostic factor associated with both cancer-specific and overall survival. 9,22 So far, factors predicting extensive LNI are critical for stratifying high-risk PCA, which needs multimodal sequential treatments. In our study, we have shown that PSA was an independent predictor of the risk of extensive LNI (more than 3 nodes) with a fair discrimination power (area under the curve .792), which represents the main feature differentiating cases with high or low metastatic load.…”
Section: Discussionmentioning
confidence: 99%